An empirical analysis of groundwater depletion in the High Plains-Ogallala Aquifer region - Hughes, Maria Vivian (Kansas State University, 2016)
Depletion of the Ogallala Aquifer is a significant concern for many communities in the High Plains region and, indeed, the global food system. Using data from 181 counties in the High Plains region, the STIRPAT model is used to identify the social drivers of groundwater depletion. The ordinary least squares regression analysis indicates that the scale of irrigation, value of agricultural commodities, and farm income each increase depletion levels, while county per capita income is negatively associated with depletion. Results from a path analysis reveal that government subsidies indirectly drive groundwater depletion by supporting farm incomes and the value of commodities. Groundwater depletion in the High Plains region is ultimately a policy decision − one that has generated a positive feedback loop linking farm incomes to groundwater withdrawals.
Keywords: agriculture; water; IPAT; Ogallala; STIRPATEnvironment